2019
DOI: 10.2147/ott.s188658
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overexpression of miR-664 is associated with poor overall survival and accelerates cell proliferation, migration and invasion in hepatocellular carcinoma</p>

Abstract: Introduction Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. This study aimed to investigate the expression patterns of microRNA-664 (miR-664) in HCC tissues and cells, and assess its clinical significance and functional role in HCC. Patients and methods One hundred and thirty-four paired HCC and non-cancerous tissues were collected from patients who underwent surgery in Qianfoshan Hospital affiliated to Shandong University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Previous studies demonstrated that miR-664-3p was closely related to the occurrence and development of a variety of tumours. [24][25][26] However, there have been no studies on the potential role of miR-664-3p in bone metabolism. In addition, two key regulators of osteogenesis, including Smad4 and Osterix (Osx), are the potential targets of miR-664-3p.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that miR-664-3p was closely related to the occurrence and development of a variety of tumours. [24][25][26] However, there have been no studies on the potential role of miR-664-3p in bone metabolism. In addition, two key regulators of osteogenesis, including Smad4 and Osterix (Osx), are the potential targets of miR-664-3p.…”
Section: Introductionmentioning
confidence: 99%
“…The modular and cellular factors that governing these processes remain unclear [21]. Multiple studies have reported that microRNAs could regulate target mRNAs and its abnormal expression was closely related to the migration, invasion, and proliferation of various cancers [10,[22][23][24]. For instance, miR-593 can inhibit the migration and invasion of non-small cell lung cancer cells by targeting SLUG-associated signaling pathways [25].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, miRNAs participate in the regulation of a variety of human proteins, which makes it easier to affect the genetic pathways [5]. Currently, miRNA has been reported to act as oncogenes or antioncogenes in the initiation and development of various cancers [6][7][8][9][10]. For example, miR-423-3p acts as an oncogene and promotes cell proliferation, migration, and invasion of lung cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“… 19 The miR-664b-3p was involved in cell progression of HCC. 20 , 21 Starbase prediction showed that the expression of miR-664b-3p was significantly down-regulated in colon adenocarcinoma. Previous study reported that miR-664b-3p overexpression inhibited the proliferation and invasion of HCC cells.…”
Section: Introductionmentioning
confidence: 99%